Aspects and problems of the Italian stock market - G. MANCINI (PSL Quarterly Review, 2014)
In the first quarter of 1948 the Italian Government issued measures of notable interest for the stock-market, regulating foreign investments, the revaluation of the capital of companies for monetary adjustment, the alleviation of certain taxes on dividends. These new measures are an important - if not conclusive - link in the work of revising the restrictions and fiscal burdens that had been accumulating in Italy during the period of war economy on investments in share-securities. The present article offers an exhaustive survey of the complicated vicissitudes of this legislation in the last ten years, of the corresponding reaction of the Italian stock-market, and of their interplay and calls attention to the characteristic features of the present situation which, after the exceptional ups and downs of the quotations in 1947, is still in a phase of expectation and uncertainty.